Comparison of calculation methods of creep coefficients and shrinkage strains based on four specifications. Issue 6 (March 2019) - Li, Lu; Zhou, Donghua; Wu, Shilong
Abstract: Formulas for calculating the creep coefficient are compared by using four specifications, in which the main influences on creep are taken into account. Nevertheless there are still a little bit differences among them. For example, the type of cement and curing temperature are not considered in the Chinese Code referred to "Code for Design of Highway Reinforced Concrete and Prestressed Concrete Bridges and Culverts (JTGD62_2004)", which in following text is abbreviated as Bridge Specification. Besides for comparison a numerical example was carried out.